Financial Accounting and Reporting: A Contemporary Emphasis (Book). - Dominiak, Gere; Siebel, Jerry D. (The Accounting Review, 1976)
Abstract Reviews the book "Financial Accounting and Reporting: A Contemporary Emphasis," by John Dearden and John Shank.